Physical and mechanical properties of nanocopper particle-reinforced alumina matrix composites - Ali, Mohammed Sabah (2017)
Over the past century, there has been a dramatic increase in fabrication and synthesizing of porous ceramics. However, only a few of them used waste material to fabricate alumina porous ceramics and reinforced it using nano-copper (Cu) particles. The motivation behind these efforts are the increasing raw materials cost and decreasing natural resources consumption which requires the use of byproducts and wastes as raw material for different industrial processes. This is a step towards environmental protection, sustainable development, and also to produce porous alumina ceramics with good porosity and mechanical properties. Thus, in this study, porous alumina ceramics were fabricated using graphite waste, natural active yeast, and rice husk ash as pore-forming agents and source of silica (SiO2). Series of porous alumina ceramics was prepared using powder metallurgy technique. The physical and mechanical properties of porous alumina ceramics with and without nano-copper (Cu) particles were measured by differential thermal analysis (DTA), energy-dispersive X-ray spectroscopy (EDX), linear shrinkage, average density (green and sintered) data measurement, and Universal Testing Machine (UTM). The average densities for both green and sintered samples decrease with increasing pore forming agent ratio for porous alumina ceramics with and without nano-copper (Cu) particles. While the linear shrinkage increases with the increase of pore forming agent ratio with and without nano-copper (Cu) particles. Besides, the structural properties of porous alumina ceramics with and without nanocopper (Cu) particles, ceramic phases, morphology, and porosity were examined using X-ray diffraction (XRD) and field-emission scanning electron microscopy (FESEM). The effects of the pore-forming agent ratios on the mechanical properties, the porosity and the microstructure with and without nano-copper (Cu) particles have been investigated in this study. The results showed that through increasing the pore-forming agent ratio for graphite waste, natural active yeast, and rice husk ash, the porosity increased from 37.3 to 61.1%, 30.2 to 63.8% and 42.9 to 49.0%, respectively. The hardness also decreased from 172.6 to 38.1 HV1 and from 160.6 to 15.0 HV1 for porous alumina ceramics using graphite waste and yeast as pore-forming agents, respectively.